Similarity in volatile communities leads to increased herbivory and greater tropical forest diversity. Issue 7 (30th June 2017) - Massad, Tara J.; Martins de Moraes, Marcílio; Philbin, Casey; Oliveira, Celso; Cebrian Torrejon, Gerardo; Fumiko Yamaguchi, Lydia; Jeffrey, Christopher S.; Dyer, Lee A.; Richards, Lora A.; Kato, Massuo J.
Abstract: A longstanding paradigm in ecology is that there are positive associations between herbivore diversity, specialization, and plant species diversity, with a focus on taxonomic diversity. However, phytochemical diversity is also an informative metric, as insect herbivores interact with host plants not as taxonomic entities, but as sources of nutrients, primary metabolites, and mixtures of attractant and repellant chemicals. The present research examines herbivore responses to phytochemical diversity measured as volatile similarity in the tropical genus Piper . We quantified associations between naturally occurring volatile variation and herbivory by specialist and generalist insects. Intraspecific similarity of volatile compounds across individuals was associated with greater overall herbivory. A structural equation model supported the hypothesis that plot level volatile similarity caused greater herbivory by generalists, but not specialists, which led to increased understory plant richness. These results demonstrate that using volatiles as a functional diversity metric is informative for understanding tropical forest diversity and indicate that generalist herbivores contribute to the maintenance of diversity.